(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
84 samples of common carp Cyprinus carpio that bird in cages of fishes birding in AlForat River Al-Mussayab was examined for a period of January until June 2017 . The fishes was examined for the presence of Ichthyophthirius multifiliis parasite on the skin, Fins and gills. The percentage and total mean intensity infection%14.28, 5.6، % 20.23, 6.2,% 27.38 11.5 respectively the monthly changes was Studied and the part of the fish body was chosen according to sex and we recording the highest percentage of infection from April 53.33% and highest intensity in August were the percentage was 21.6%. There was no recording of differences in chosen of site of infection and also in sex and host either in skin, Fins and gills.